Community empowerment and scaling-up in urban areas: the evolution of Push/Prospect in Zambia - Garrett, James L. (International Food Policy Research Institute, 2004)
CARE began PROSPECT (Program of Support for Poverty Elimination and Community Transformation) in 1998. PROSPECT aims to reduce poverty in peri-urban areas of Lusaka. It employs a community-based approach to carry out three types of activities: social empowerment (institution building at the local level), personal empowerment (microfinance), and infrastructure improvement (mostly water supply schemes). PROSPECT has attempted to carry out these activities largely through its support of area-based organizations (ABOs) that now form part of city government. The zone development committees (ZDCs) and residents' development committees (RDCs) are the basic components of the ABO structure. These are community-level representations of municipal government; they are the community's mechanisms for expressing its voice and driving development. PROSPECT is itself an extension of an earlier project, PUSH II (Peri-Urban Self-Help Project). PUSH II and PROSPECT are fundamentally about developing community-based and community-driven development (CDD) mechanisms and strengthening community capacities to identify and respond to community needs. The paper examines the scaling-up experience of PUSH II and PROSPECT, looking especially at the mechanisms of CDD, the ABOs.